CLINICAL-EPIDEMIOLOGICAL ANALYSIS OF PATIENTS WITH CERVICALGIA AND THE IMPACT OF NUCLEAR RESONANCE - Muryllo Henrique Ferreira de Brito; Karllos Adryano Priscinotte Rodrigues Lima; Pedro Pereira Barbosa; Newton Antônio Tristão (Acta Ortopédica Brasileira)
ABSTRACT Objective: To analyze the clinical and epidemiological profile of patients with neck pain, assessing risk factors, comorbidities, and the need for therapeutic interventions, as well as the impact of magnetic resonance imaging (MRI) on case management. Methods: This is a cross-sectional study involving 435 patients treated at the Emergency Department of the Instituto Ortopédico de Goiânia (IOG) between July and December 2023. Sociodemographic, clinical, and risk factor variables were analyzed based on data collected from electronic medical records. Statistical analysis included association tests with a significance level of 5% (p<0.05). Results: A high prevalence of sedentary lifestyle (94.59%) and prolonged work exposure (78.38%) was observed. Most patients required medication (94.59%), while 63.96% underwent additional clinical interventions. Statistically significant associations were identified between sex, occupational factors, and lesions detected by MRI. The average time to diagnosis was 4.2 months. Conclusion: Neck pain is strongly associated with modifiable risk factors such as sedentary behavior and occupational overload, highlighting the importance of preventive strategies and individualized therapeutic approaches. MRI played a key role in diagnosis and treatment planning. Level of Evidence III; Study of Non-Consecutive Patients; No Uniformly Applied "Gold" Reference Standard.